DIGITAL GAP ANALYSIS IN THE USE OF MOBILE BANKING APPLICATIONS IN THE CITY OF BANDUNG - Kharisma, Ryan Hafizh; Giri, Refi Rifaldi Windya (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This research discusses the digital divide in the use of mobile banking applications in the city of Bandung, Indonesia, where the use of mobile banking is still relatively minimal compared to other bank services. The study aims to analyze the digital divide based on four stages of using digital technology, which are motivation, physical access and material access, mobile banking skills, and usage. The author uses quantitative methods with the PLS-SEM multivariate analysis technique to determine the relationship between predetermined variables. For data processing, the author uses WarpPLS 8.0 where the data processed is based on samples taken through non-probability sampling using the purposive sampling method with a total of 300 respondents taken from part of the population of Bandung City who use mobile banking applications. Based on research that has been carried out by the author, it was obtained that the variables motivation, physical access and material access, mobile banking skills, and usage are stated to be significant. This shows that there is no digital divide in the use of mobile banking applications in the city of Bandung.